ANALISIS PENGARUH SUHU TERHADAP TEGANGAN TEMBUS MINYAK PELUMAS 15W-40 JENIS SINTETIS DAN NON SINTETIS - Rifai, Muhamad Rifai Damogalad; Faiz Farhan Mohamad; Lanto Moh Kamil Amali (Lafadz Jaya Publisher, 2023)
Engine lubricating oil or better known as engine oil is a substance that serves to lubricate the engine. All types of oil are basically the same. Namely as a lubricant so that the engine runs smoothly and hassle free. It also functions as a cooler and insulator. Oil contains fine layers, serves to prevent the occurrence of collisions between metal and metal engine components to a minimum, preventing scratches or wear. Breakdown is an event when the magnetic field is increased (voltage is continuously increased), the atoms will ionized and up to the limit of the insulator's ability to withstand the voltage, the insulator will turn into a conductor. The purpose of this study was to determine whether there is an effect of temperature changes on the breakdown voltage value of engine oil when heating occurs in synthetic and non-synthetic engine oil. The method used is the experimental method. The research subjects that will be studied are synthetic and non-synthetic type 15w-40 oil in new condition. In data collection, 15w-40 mineral and synthetic oil samples were taken and then tested at normal temperature three times then the oil was heated and samples were taken at every 120℃, 90℃, 60℃ and at the initial temperature after being heated and each sample was carried out three times. The test is carried out based on the SPLN Test Standard 49-1 with the IEC 156 test method, a transformer oil as an insulating material must have a minimum breakdown voltage of 30kV/2.5mm.